2014
DOI: 10.1590/s1516-14392014005000044
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of CaCO3 and microstructure of the shell of a Brazilian invasive mollusc (Limnoperna fortunei)

Abstract: Applying the theories of Materials Science and Engineering to describe the composition and hierarchy of microstructures that comprise biological systems could help the search for new materials and results in a deeper insight into evolutionary processes. The layered microstructure that makes up the freshwater bivalve Limnoperna fortunei shell, an invasive specie in Brazil, was investigated utilizing SEM and AFM for the determination of the morphology and organization of the layers; and XRD was used to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 22 publications
4
20
0
Order By: Relevance
“…The need for biocompatible materials for clinical use has become of a growing concern, the focus of much of the recent biomedical research [4][5][6][7][8][9] . What would be the ideal material for the substitution or regeneration of damaged bone tissue?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The need for biocompatible materials for clinical use has become of a growing concern, the focus of much of the recent biomedical research [4][5][6][7][8][9] . What would be the ideal material for the substitution or regeneration of damaged bone tissue?…”
Section: Introductionmentioning
confidence: 99%
“…In mollusc shells, the aragonite and the protein matrix form a composite material (mineral matrix + organic matrix) called nacre. Taking into account that the mechanisms behind the construction of the different biomineralized tissues occur in similar fashion, it seems coherent to seek out materials that can substitute or induce the regeneration of bone tissue in other biomineralizing organisms, and this explains the attention given to corals and molluscs with shells 5,6,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] . Thus, this work has sought, through the gathering and comparison of the characteristics of clinical interest, to find in the residues from malacoculture the potential for obtaining an industrial input of low ecological/economic impact.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of hearing, fish with larger, vateritic, and/or otherwise asymmetrical sagittae exhibited reduced sensitivity or deafness (Oxman et al, 2007; Gagliano et al, 2008; Browning et al, 2012); some presumably because vaterite is less dense than aragonite, thereby reducing otolith displacement amplitude and effectiveness in the inner ear (Bignami et al, 2013; Reimer et al, 2016). Although there remains no evidence of ocean acidification-induced vaterite replacement in otoliths, including in A. clarkii , there is some evidence for calcite replacement in sagittae and lapilli at elevated pCO 2 (Coll-Lladó et al, 2018); calcite is similarly less dense than aragonite (Nakamura Filho et al, 2014). In terms of kinesthesia, some fish with abnormal and/or asymmetric sagittae/lapilli exhibited kinetoses (Söllner, 2003; Anken, Knie & Hilbig, 2017); however, other studies observed pCO 2 impacts on otolith morphology without observing impacts on behavior (Bignami, Sponaugle & Cowen, 2013; Bignami, Sponaugle & Cowen, 2014; Shen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The full morphological knowledge of L. fortunei structures is important to highlight the understanding of bioinvasion aspects. Some recent studies focused on the functional surface of the foot [8] and of the shell microstructure of L. fortunei [9]. As a proli c lter feeder, the clearance rates of the golden mussel are among the highest reported for suspension feeding bivalves, including other invasive species such as Dreissena polymorpha (Pallas 1771), Dreissena bugensis (Andrusov 1897), and C. uminea [10].…”
Section: Introductionmentioning
confidence: 99%
“…Morphologically, L. fortunei is a headless mollusk that has a single foot enclosing the visceral mass, two pairs of gills (ctenidia) and gonochoric with external fertilization. Each individual has two valves surrounding the body composed of calcium carbonate [16] and its polymorphs aragonite and amorphous calcium carbonate [9]. Gills are in direct contact with the environment, suggesting their importance in xenobiotics biotransformation, antioxidant response, signal transduction, innate immune response, and osmoregulation [17,18].…”
Section: Introductionmentioning
confidence: 99%